2016
DOI: 10.3390/ijerph13100989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bisphenol A on Type 2 Diabetes Mellitus

Abstract: Bisphenol A (BPA) is an organic synthetic compound employed to produce plastics and epoxy resins. It is used as a structural component in polycarbonate beverage bottles and as coating for metal surface in food containers and packaging. The adverse effects of BPA on human health are widely disputed. BPA has been recently associated with a wide variety of medical disorders and, in particular, it was identified as potential endocrine-disrupting compound with diabetogenic action. Most of the clinical observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 70 publications
0
44
0
4
Order By: Relevance
“…The estimated daily intake for adults is around 1.5 μg/kg bw/day. Moreover, WHO, Food and Drug Administration (FDA) and European Food Safety Authority (EFSA), based on rodent studies, have also determined the no adverse effect level (NOAEL) for the systemic toxicity of BPA in animals, corresponding, for dietary exposure, to 5 mg/kg bw/day [13,47]. In consideration of the differences in toxicokinetics among the species, EFSA, on grounds of prudence, applied a default uncertainty factor of 100 to the overall NOAEL and of 1000 to the overall LOAEL, establishing a TDI of 0.05 mg/kg bw (50 μg/kg bw/day) for humans over the life-time [13].…”
Section: Bisphenol a As Endocrine Disruptor Chemical: Mechanisms Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated daily intake for adults is around 1.5 μg/kg bw/day. Moreover, WHO, Food and Drug Administration (FDA) and European Food Safety Authority (EFSA), based on rodent studies, have also determined the no adverse effect level (NOAEL) for the systemic toxicity of BPA in animals, corresponding, for dietary exposure, to 5 mg/kg bw/day [13,47]. In consideration of the differences in toxicokinetics among the species, EFSA, on grounds of prudence, applied a default uncertainty factor of 100 to the overall NOAEL and of 1000 to the overall LOAEL, establishing a TDI of 0.05 mg/kg bw (50 μg/kg bw/day) for humans over the life-time [13].…”
Section: Bisphenol a As Endocrine Disruptor Chemical: Mechanisms Of Amentioning
confidence: 99%
“…BPA is metabolized and inactivated through glucuronidation by uridine diphosphate glucuronosyltransferases and sulfation, by phenolsulfotransferases in hepatocytes microsomes. The conjugated, glucuronidated and sulfated, inactive forms of BPA acquire hydrophilic characteristics and are excreted into the bile and urine, with a half-life corresponding to around 6 hours [47][48][49]. Nevertheless, the expression of β-glucuronidase enzyme, a member of the glycosidase family of enzymes which cleave the glucuronide group from the metabolite via hydrolysis, in several tissues, like lungs, liver, kidneys and placenta of animals and humans, ensures deconjugation of BPA and therefore the release of its active form into the blood and again its distribution into the body [50].…”
Section: Bisphenol a As Endocrine Disruptor Chemical: Mechanisms Of Amentioning
confidence: 99%
“…Among the list of known and suspected environmental toxicants, bisphenol A (BPA) and its derivatives, 1 including bisphenol S (BPS) and bisphenol F (BPF), 2 have received a significant amount of attention in both the scientific literature 3 and the popular media. BPA is a suspected endocrine disruptor, 4 and exposure to BPA and associated derivatives is correlated with increased rates of asthma, 5 inflammatory bowel disease, 6 endocrine disorders, 7 and certain cancer sub-types. 8 These negative health effects are particularly concerning because of BPA's ubiquitous presence in a variety of commercial products, including plastic water bottles 9 and bags, 10 liners of canned food products, 11 infant bottles 12 and training (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Significant exposure often occurs by consuming food and beverages contaminated with BPA and in dental procedures, so that up to 92.6% of the human population has detectable BPA levels in their bodies 3,4 . Epidemiological studies have demonstrated that higher BPA urine concentrations are associated with increased morbidity and mortality from cardiovascular diseases 5,6 , and several studies in humans and animal models have suggested a causative role for BPA in cardiovascular disease including hypertension, atherosclerosis, cardiac hypertrophy and arrythmias [7][8][9][10] . Recently, it has been reported that a life long exposure to BPA in rodents produces arrhythmogenic effects 11 .…”
mentioning
confidence: 99%